Efficacy of a single injection compared with triple injections using a costoclavicular approach for infraclavicular brachial plexus block during forearm and hand surgery: A randomized controlled trial. Issue 43 (23rd October 2020) - Lee, Mi Geum; Jung, Wol Seon; Go, Doo Yeon; Choi, Sung Uk; Shin, Hye Won; Choi, Yun Suk; Shin, Hyeon Ju
Abstract: Objectives: It was recently proposed that a costoclavicular (CC) approach can be used in ultrasound (US)-guided infraclavicular brachial plexus block (BPB). In this study, we hypothesized that triple injections in each of the 3 cords in the CC space would result in a greater spread in the 4 major terminal nerves of the brachial plexus than a single injection in the CC space without increasing the local anesthetic (LA) volume. Methods: Sixty-eight patients who underwent upper extremity surgery randomly received either a single injection (SI group, n = 34) or a triple injection (TI group, n = 34) using the CC approach. Ten milliliters of 2% lidocaine, 10 mL of 0.75% ropivacaine, and 5 mL of normal saline were used for BPB in each group (total 25 mL). Sensory-motor blockade of the ipsilateral median, radial, ulnar, and musculocutaneous nerves was assessed by a blinded observer at 5 minutes intervals for 30 minutes immediately after LA administration. Results: Thirty minutes after the block, the blockage rate of all 4 nerves was significantly higher in the TI group than in the SI group (52.9% in the SI group vs 85.3% in the TI group, P  = .004). But there was no significant difference in the anesthesia grade between the 2 groups ( P  = .262). The performance time was similar in the 2 groups (3.0 ± 0.9 minutes in the SI group vs 3.2 ± 1.2 minutes in the TI group, respectively; P  = .54). Discussion: The TI of CC approach increased the consistency of US-guided infraclavicular BPB in terms of the rate of blocking all 4 nerves without increasing the procedure time despite administering the same volume of the LA.